Human Telomerase RNA Protein Encoded by Telomerase RNA is Involved in Metabolic Responses - Shliapina, Viktoriia; Koriagina, Mariia; Vasilkova, Daria; Govorun, Vadim; Dontsova, Olga; Rubtsova, Maria (Frontiers in Cell and Developmental Biology, 2021)
Cell proliferation is associated with increased energy and nutrients consumption. Metabolism switch from oxidative phosphorylation to glycolysis and telomerase activity are induced during stimulation of proliferation, such as tumorigenesis, immune cell activation, and stem cell differentiation, among others. Telomerase RNA is one of the core components of the telomerase complex and participates in survival mechanisms that are activated under stress conditions. Human telomerase RNA protein (hTERP) is encoded by telomerase RNA and has been recently shown to be involved in autophagy regulation. In this study, we demonstrated the role of hTERP in the modulation of signaling pathways regulating autophagy, protein biosynthesis, and cell proliferation. The AMPK signaling pathway was affected in cells deficient of hTERP and when hTERP was overexpressed. The appearance of hTERP is important for metabolism switching associated with the accelerated proliferation of cells in healthy and pathological processes. These findings demonstrate the connection between telomerase RNA biogenesis and function and signaling pathways.